2021
DOI: 10.1001/jamainternmed.2020.5008
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences Entangling With Electronic Health Record Documentation

Abstract: high-dose colchicine in the treatment of acute gout. 4 Consistent with the recommendations of the European League Against Rheumatism, low-dose colchicine was found to be equally effective as high-dose drug in the reduction of gouty pain; the rate of gastrointestinal adverse events with lowdose colchicine was one-third that observed with high-dose colchicine. In response to these study findings, the FDA approved Colcrys, which, consequently, became the first colchicine product to ever be approved for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In previous research, while female physicians reported similar numbers of medically complex patients, they reported greater numbers of psychosocially complex and frustrating patients. 3 Patient-level data would enable further evaluation of whether patient complexity explains the gender differences in EHR care, and whether adjusting panelsize expectations for patient complexity would reduce gender differences in workload. Fourth, we used the hospital physician database to identify physician gender, which at the time of this study required respondents to categorize themselves as either male or female; therefore, we could not capture information on physicians who were transgender or nonbinary; similar limitations at the time applied to available patient gender (legal gender as listed in Epic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, while female physicians reported similar numbers of medically complex patients, they reported greater numbers of psychosocially complex and frustrating patients. 3 Patient-level data would enable further evaluation of whether patient complexity explains the gender differences in EHR care, and whether adjusting panelsize expectations for patient complexity would reduce gender differences in workload. Fourth, we used the hospital physician database to identify physician gender, which at the time of this study required respondents to categorize themselves as either male or female; therefore, we could not capture information on physicians who were transgender or nonbinary; similar limitations at the time applied to available patient gender (legal gender as listed in Epic).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that female physicians spend more time working in the electronic health record (EHR) than do male physicians. [1][2][3] This increased EHR time may contribute to the documented higher rates of burnout among female physicians nationwide compared with their male colleagues. 4 In particular, time spent in the EHR inbasket, within which physicians respond to messages from patients, staff, and colleagues, has been linked to burnout.…”
Section: Introductionmentioning
confidence: 99%
“…3 Information Management Group, Centre for Addiction and Mental Health, Toronto, ON, Canada. 4 Lunenfeld-Tanenbaum Research Institute, Sinai Health, Toronto, ON, Canada. 5 Bloomberg Faculty of Nursing, University of Toronto, Toronto, ON, Canada.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Nurses represent the largest group of healthcare providers in Canada and have been reported to be the primary users of EHR systems [1,2]. While EHR systems serve as the backbone of documentation for all clinical activities [3], studies have shown that nurses spend a greater amount of time documenting their assessments, care, and outcomes in the EHR now than in the past [4,5]. While previous initiatives have focused on expanding the design and functionalities of EHRs for research purposes to support clinical decision-making and assist with patient risk assessments [6][7][8][9], the growing burden caused by documentation requirements has overshadowed these efforts and led to inefficiencies in the EHR, taking time away from patient care activities and reducing joy in the profession [7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%